Characteristics of Diabetic Cataract Patients at Siti Rahmah Padang Hospital, 2018-2019 - Farah Diba Lazuardi; Haves Ashan (Science Midwifery, 2022)
Diabetic cataracts appear as a result of diabetes mellitus. A person's likelihood of developing cataracts is 25 times higher for people with diabetes mellitus compared to healthy people. Diabetic cataracts are caused by changes in the pathway of sorbitol in the lens of the eye. This change in trajectory will then injure the osmotic cells to cause an image of opacity in the lens of the eye. The purpose of this study was to determine the characteristics of diabetic cataract patients who were at the Siti Rahmah Islamic Hospital Padang in 2018-2019. The population of this study were cataract patients who had a history of type 2 diabetes mellitus at the Islamic Hospital Siti Rahmah Padang in 2018-2019. Meanwhile, the sample used was 37 people. Univariate analysis is shown in the form of a frequency distribution table. The results of this study found that the most characteristic of cataract patients were the age group 56-65 years as many as 16 people (43.2%), female sex as many as 22 people (59.5%), blood glucose levels when <300 mg/dl as many as 22 people (59.5%), and had suffered from diabetes mellitus for >5 years as many as 20 people (54.1%). Based on the results of the study, it can be concluded that the highest age is 56-65 years, the most gender is female, the highest blood glucose level is <300 mg/dl, and the duration of diabetes mellitus is <5 years.